Cuentos de mi Tía Panchita como una manifestación del género denominado literatura infantil - Pacheco Acuña, Gilda (2004)
This article discusses the nature of the literary genre known as Children's literature and emphasizes three aspects: the presence of folkloric elements, the conflict between reality and fantasy and the objective or aim of children's texts. Cuentos de mi Tía Panchita serves as an illustrative literary text that facilitates the exploration of such themes.